Integration of Host Plant Resistance and Cultural Tactics for Management of Root- and Stem-Feeding Insect Pests in Rice - Villegas, James M.; Wilson, Blake E.; Stout, Michael J. (Frontiers in Agronomy, 2021)
The rice water weevil, Lissorhoptrus oryzophilus Kuschel, is the most important early-season pest of rice in the U.S. Additionally, lepidopteran stem-boring pests particularly the invasive Mexican rice borer, Eoreuma loftini (Dyar), are increasingly becoming problematic in Louisiana rice. Although insecticidal seed treatments have been widely adopted and have proven highly effective against weevils and stemborers, alternative management tactics are needed. This study was conducted to evaluate the effects of flood timing and rice cultivar on rice water weevil and stemborer infestations. Field experiments were conducted in Crowley, Louisiana, from 2019–2020. In each year, early- and late-planted trials were established according to a split-split-plot randomized block design. Four commonly grown rice cultivars were selected and were either treated or not treated with a chlorantraniliprole seed treatment. Permanent flood was established at normal timing (approximately the five-leaf stage) or delayed by two weeks. Seed treatment reduced weevil densities and stemborer injury by 70–84% and 87–94%, respectively, across planting dates, years, cultivars, and flood timings. The rice cultivar ‘Jupiter’ consistently supported the highest numbers of immature weevils, whereas low levels of stemborer injury were observed in ‘Jazzman-2’. Weevil densities were 72% and 20% lower in plots subjected to delayed flood compared to normal flood timing in the 2019 and 2020 late-planted trials, respectively. Reductions of 79% and 93% in stemborer injury in the 2019 early- and late-planted trials, respectively, were observed in delayed flooded plots. Weevil and stemborer infestations negatively affected rice yields, with losses among cultivars ranging from 14–49%. Yield losses were generally lower in plots subjected to delayed flood compared to normal flood timing but the difference was only significant in the 2020 late-planted trial. Our data suggest that the combination of cultivar resistance and delayed flooding can serve as a valuable component of an integrated pest management program for both rice water weevil and stemborers.